Jabatan Kerja Raya Daerah Segamat / Izzul Arifin Ishak - Ishak, Izzul Arifin (Faculty of Civil Engineering, 2018)
Properly executed and evaluated industrial training helps a lot in developing a professional attitude. It develop an awareness of industrial approach to problem solving, based on a broad under-standing of process and mode of operation of organization. During a period of two month training at Jabatan Kerja Raya (JKR) in Segamat, most of the theoretical knowledge that has been gained during the course of studies is put to test. Some of the process of lab procedure have been learned before the industrial training programmed starts such cube test and sand replacement test was used during this internship. The cube test have been used during inspection for project slope maintenance at Jalan Kuantan, Segamat. The purpose of making the test is to determine whether the strength of the concrete that used for the project is achieved the strength needed. Not only that, sand replacement also have been learnt during semester 4 in soil material course and have been applied in working environment. Thus, it shows that knowledge is important in working. Final report will be divided into few chapters. Chapter 1 includes background of the company which is JKR's background. Next, the organizational chart for all department in this company and the nature of business also will be given. For chapter 2, the content will be processed about weekly summary of 8 weeks of internship. Chapter 3 is technical report, where the content will be the project that student attend and learned. The project that have been through by the student were the treatment of damage road, the crematorium project with 1 cremator, the construction of new road and the process making retaining wall at existing drains. Lastly, the report will have the conclusion where it will be conclude for the student activity during industrial training.